PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY BERDASARKAN TINGKAT PROFITABILITY, CORPORATE SIZE, DAN LEVERAGE (Studi Empiris pada Perusahaan Food and Beverage yang Terdaftar di BEI Tahun 2018-2021) - Anisa Yani Ardi Saputri; Yuli Tri Cahyono (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine the disclosure of corporate social responsibility based on the level of profitability, corporatey size, and leverage. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The sampling technique used was purposive sampling method and a sample of 95 companies was obtained. The data analysis method used was multiple linear regression analysis with SPSS 25. The results showed that the variable profitability proxied by ROA, corporate size proxied by SIZE, and leverage proxied by DER had an effect on the disclosure of corporate social responsibility.